THE RELATIONSHIP OF READING INTEREST TO STUDENTS’ LEARNING ACHIEVEMENT IN 4TH GRADE ELEMENTARY SCHOOL - Nur Annisa; Kiki Aryaningrum; Ali Fakhrudin (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2022)
Abstract The reading interest of students in 4th-grade of SDN 16 Muara Enim is still low. There are still few students who visit the library. So it makes students' achievement decrease. Of 21 students who scored below the minimum completeness criteria were 52%. One of the factors is the lack of parental supervision and environmental factors. The purpose of the research was to determine the existence of a positive and significant relationship between reading interest and students' achievement in 4th-grade of SDN 16 Muara Enim. The research method is a quantitative method with a correlational approach. The results of the research using SPSS 25.0 showed that the results of reading interest from the distribution of questionnaires from all respondents of 21 students with a total of r count 0.436 and the t table seen from the 5% significance level were 0.433. According to the provisions, if rcount is bigger than rtable then Ha is accepted and vice versa if rcount is smaller than rtable then Ho is accepted. So it can be concluded that there is a positive and significant relationship between reading interest and learning achievement of 4th-grade students at SDN 16 Muara Enim. Keywords: Reading Interest; Learning Achievement